2002
DOI: 10.1108/00070700210434589
|View full text |Cite
|
Sign up to set email alerts
|

The market information system and state support for the market of agricultural products in Croatia

Abstract: Most of transitional (former socialist) countries still suffer from underdeveloped market mechanisms. In order to provide support for development of modern market mechanisms for the market of agricultural products, government experts within the Ministry of Agriculture and Forestry designed institutional information support – Market Information System in Agriculture of the Republic of Croatia – TISUP. This system is organised in order to prevent one of the most important market failures – insufficient and delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Furthermore, market linkages ensure that farmers negotiate from a position of greater strength which enables them to improve household income and livelihood. The finding of this study is supported by Renko et al (2002) who reported that in Croatia farmers accessed government market support and this helped to improve agrarian structures, competiveness of local producers and identification, introduction and application of modern technologies Inferential statistics results (β2= -0.037 and p=0.351) depicted that p > 0.05 thus the null hypothesis was accepted. This implies that for every unit increase in government agricultural support programs there was no corresponding improvement in livelihood of smallholder vegetable farmers.…”
Section: Characteristics Of Vegetable Farmingsupporting
confidence: 69%
“…Furthermore, market linkages ensure that farmers negotiate from a position of greater strength which enables them to improve household income and livelihood. The finding of this study is supported by Renko et al (2002) who reported that in Croatia farmers accessed government market support and this helped to improve agrarian structures, competiveness of local producers and identification, introduction and application of modern technologies Inferential statistics results (β2= -0.037 and p=0.351) depicted that p > 0.05 thus the null hypothesis was accepted. This implies that for every unit increase in government agricultural support programs there was no corresponding improvement in livelihood of smallholder vegetable farmers.…”
Section: Characteristics Of Vegetable Farmingsupporting
confidence: 69%
“…Development of agriculture information system can be referenced to those three phases. Implementation of Information System in Agriculture has been implemented in Kenya (Rees, Momanyi, Wekundah, Ndungu, & Odondi, 2000), Croatia (Renko, Nikalosevic, & Pavicic, 2002), China (Wen, Zetian, Daoliang, Longyong, Jian, & Xiashuan, 2007). Table 1 shows some information system that is successfully developed in many countries.…”
Section: Agriculture Information Systemmentioning
confidence: 99%